Bessy has 6 times as much money as Bob. But when each earns $6, Bessy will have 3 times as much money as Bob. How much does each have before and after earning the $6?
Let x be Bob's money, then Bessy's money is 6x
When Bob earns 6 dollars, his money becomes x + 6
When Bessy earns 6 dollars his money becomes 6x + 6
Now Bessy has 3 times as much money as Bob
so the equation is
6x + 6 = 3 * (x + 6)
6x + 6 = 3x + 18
6x + 6 - 6 = 3x + 18 - 6
6x = 3x + 12
6x - 3x = 3x - 3x + 12
3x = 12
x = 4
Before Bob and Bessy earned 6 dollars, Bob had 4 dollars and Bessy has 6 x 4 = 24
After they both earned 6 dollars, Bob had 10 dollars and and Bessy had 30 dollars.
Indeed 30 is 3 times 10.
Comments for Bessy and Bob algebra word problem
Click here to add your own comments
Join in and write your own page! It's easy to do. How? Simply click here to return to Algebra word problems.
Jun 06, 23 07:32 AM
May 01, 23 07:00 AM